Plastic Buckling Paradox: An Updated Review - Shamass, Rabee (Frontiers in Built Environment, 2020)
It is widely accepted that the flow theory of plasticity either fails to predict buckling or significantly overestimates buckling stresses and strains, while the deformation theory, which lacks physical rigour compared to the flow theory, provides results that are more in line with experimental findings and is therefore generally recommended for use in practical applications. This paper aims to review the reasons behind the seeming differences between the predictions provided by these two theories, and therefore provide some explanation of this so-called ‘plastic buckling paradox’.